Paleolithic Open-air Sites, North of Susiana Plain in South West Iran, Khuzestan Province, East of Dez River. (20th May 2015) - Dinarvand, Yusef; Mehranpour, Hadi
Khuzestan province bears most of cultural periods since ten thousand years ago (the Holocene). This period relates to Khuzestan plain but up to now, little work has been done on the Pre-Holocene periods and there is no information of the Paleolithic hunter-gatheres groups all around this plain. Due to permanent and abundant rivers such as Dez and Karkheh, the rich flora and fauna around them and also abundant raw materials for making tools, made the north and northeastern heights of Khuzestan very favorable environments for the presence of Pleistocene hominin groups.